Removal of natural anti-αGal antibodies elicits protective immunity against Gram-negative bacterial infections - Olivera-Ardid, Sara; Bello-Gil, Daniel; Perez-Cruz, Magdiel; Costa, Cristina; Camoez, Mariana; Dominguez, M. Angeles; Ferrero-Alves, Yara; Vaquero, Jose Miguel; Khasbiullina, Nailya; Shilova, Nadezhda V.; Bovin, Nicolai V.; Mañez, Rafael (Frontiers in Immunology, 2023)
Antibody-dependent enhancement (ADE) of bacterial infections occurs when blocking or inhibitory antibodies facilitate the infectivity of pathogens. In humans, antibodies involved in ADE of bacterial infections may include those naturally produced against Galα1-3Galβ1-4GlcNAcβ (αGal). Here, we investigate whether eliminating circulating anti-αGal antibodies using a soluble αGal glycopolymer confers protection against Gram-negative bacterial infections. We demonstrated that the in vivo intracorporeal removal of anti-αGal antibodies in α1,3-galactosyltransferase knockout (GalT-KO) mice was associated with protection against mortality from Gram-negative sepsis after cecal ligation and puncture (CLP). The improved survival of GalT-KO mice was associated with an increased killing capacity of serum against Escherichia coli isolated after CLP and reduced binding of IgG1 and IgG3 to the bacteria. Additionally, inhibition of anti-αGal antibodies from human serum in vitro increases the bactericidal killing of E. coli O86:B7 and multidrug-resistant Klebsiella pneumoniae and Pseudomonas aeruginosa. In the case of E. coli O86:B7, there was also an improvement in bacteria opsonophagocytosis by macrophages. Both lytic mechanisms were related to a decreased binding of IgG2 to the bacteria. Our results show that protective immunity against Gram-negative bacterial pathogens can be elicited, and infectious diseases caused by these bacteria can be prevented by removing natural anti-αGal antibodies.